Dinoflagellate planktonic-motile-stage and benthic-cyst assemblages from a monsoon-influenced tropical harbour: Elucidating the role of environmental conditions. (15th October 2019) - Rodrigues, R.V.; Patil, J.S.; K, Sathish; Anil, A.C.
Abstract: Dinoflagellates are referred among potential bioinvaders and environmental proxies. Information from tropical regions on the coupling of cyst and motile stages of dinoflagellates characterized by high suspended-load, and high diversity but low abundance is limited. Here, the population dynamics of dinoflagellates (planktonic-motile-stages and benthic-cysts) from monsoon-influenced Cochin-harbour, southwest coast of India was investigated. A targeted sampling strategy is proposed over conventional methods to obtain better estimates of abundance and diversity. From the water column, the cyst-producing-dinoflagellates contribution was quantified for the first time, and it was up to 52% of total planktonic-motile-stages. Interestingly, the number of motile-stages versus the number of cysts for heterotrophs revealed an inverse trend and the explanation is not straightforward. This is because Cochin-harbour experiences discharges, i.e., freshwater (peak during monsoon), anthropogenic, and dredging activities throughout the year facilitating benthic-suspension, high sedimentation rate, and distinct seasonality in the availability of prey. In such an environment, motile-stages-diversity and cysts-species-richness formed potential environmental proxies. The presence of cysts of indicator taxa ( Protoperidinium, Polykrikos, Lingulodinium ) for nutrient-enrichment in relatively good proportions and low ranges of motile-stages diversity and cysts species-richness do signal eutrophic system. Autotrophic-cysts dominance illustrates that the heterotrophs need not be dominant in the eutrophic-system as reported in earlier studies. The dominance of euryhaline dinoflagellates ( Gonyaulax spinifera, Protoperidinium pentagonum, P. leonis, Pyrophacus steinii ) cysts provided additional information on cyst-producing-dinoflagellates as potential environmental indicators. The existence of 24 morphotypes belonging to potentially harmful-algal-bloom (HAB) species emphasizes HAB risks under favorable conditions. Graphical abstract: Image 1 Highlights: Dinoflagellate motile-stages (MS) & cysts distribution in a monsoonal harbour. Observed inverse relationship between benthic-cysts & planktonic-MS abundance. MS diversity & cysts species-richness as potential environmental proxies. Heterotrophic cysts need not be dominant in the eutrophic system. Indicator taxa existence for salinity and eutrophication.